2007
DOI: 10.1086/521710
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Phylogeny of the Fern Family Dryopteridaceae Inferred from ChloroplastrbcL andatpB Genes

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. The University of Chicago Press is collaborating with JSTOR to digitize, preserve and extend access to International Journal of Plant Sciences.Dryopteridaceae are a large fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
64
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 38 publications
12
64
0
4
Order By: Relevance
“…Dryopteridaceae (i.e., Arachniodes, Bolbitis, Cyrtomium, Dryopteris, Elaphoglossum, Mickelia, Phanerophlebia, Polystichopsis, and Polystichum) are strongly supported as monophyletic (PP BI = 1; BS ML = 94, JK MP = 89, PP BEAST = 0.99, Figs. 1a and 2, S1-S4), which is consistent with previous studies (Liu et al, 2007;Schuettpelz and Pryer, 2007). Within Dryopteridaceae, the polystichoid ferns (Cyrtomium, Phanerophlebia, and Polystichum), constitute a strongly supported clade (Figs.…”
Section: Phylogenetic Analysessupporting
confidence: 89%
See 1 more Smart Citation
“…Dryopteridaceae (i.e., Arachniodes, Bolbitis, Cyrtomium, Dryopteris, Elaphoglossum, Mickelia, Phanerophlebia, Polystichopsis, and Polystichum) are strongly supported as monophyletic (PP BI = 1; BS ML = 94, JK MP = 89, PP BEAST = 0.99, Figs. 1a and 2, S1-S4), which is consistent with previous studies (Liu et al, 2007;Schuettpelz and Pryer, 2007). Within Dryopteridaceae, the polystichoid ferns (Cyrtomium, Phanerophlebia, and Polystichum), constitute a strongly supported clade (Figs.…”
Section: Phylogenetic Analysessupporting
confidence: 89%
“…A more detailed analysis of these genera will be published separately. Based on previous molecular (e.g., Little and Barrington, 2003;Li et al, 2004Li et al, , 2008Driscoll and Barrington, 2007;Schuettpelz and Pryer, 2007;Lu et al, 2007;Liu et al, 2007) and morphological studies (Smith et al, 2006;Zhang et al, 2013), four species of Elaphoglossum Schott, two of Mickelia R.C. Moran, Labiak & Sundue, one of Bolbitis Schott, eight of Dryopteris Adans., four of Arachniodes Blume, and two of Polystichopsis (J.…”
Section: Taxon Samplingmentioning
confidence: 99%
“…Elaphoglossaceae and Peranemataceae were later combined with Dryopteridaceae and the latter given nomenclatural preference (Pichi-Sermolli 1970b). Subsequent phylogenetic analyses (Li and Lu 2006a, b;Liu et al 2007) have identified four major lineages in Dryopteridaceae, which is now recognized as containing ca. 25 genera .…”
Section: The Genus Dryopterismentioning
confidence: 99%
“…The relationships between Dryopteris and Nothoperanema (Tagawa) Ching, Acrophorus C. Presl, Diacalpe Blume, and Peranema D. Don have been particularly problematic; the latter three genera have together been considered a separate family (the Peranemataceae, sensu Ching 1978), and Nothoperanema a subgenus of Dryopteris (Tagawa 1938). In addition, several authors have recently found Dryopteris to be paraphyletic relative to Acrorumohra (H. Itô) H. Itô, Dryopsis Holttum & P. J. Edwards, and Revwattsia D. L. Jones (Li and Lu 2006b;Liu et al 2007;McKeown et al 2012). Several groups have recently taken steps toward a revision of the genus based on these phylogenetic analyses: To date, no exhaustive phylogenetic analysis of all 350 + species of Dryopteris has been undertaken.…”
mentioning
confidence: 99%
“…Morphologically most species of Elaphoglossum can be easily distinguished from other fern genera by their simple entire leaves, acrostichoid sori, transversely elongated ventral meristele in the rhizomes, dimorphic fertile and sterile leaves, and free veins. The monophyly of the genus and its placement within Dryopteridaceae have received strong support from several molecular phylogenetic studies , Liu et al 2007, Schuettpelz & Pryer 2007, Moran et al 2010). …”
Section: Introductionmentioning
confidence: 99%